2006
DOI: 10.1007/s00223-005-0234-1
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Insulin and Insulin-Like Growth Factors I and II on Osteoprogenitors and Adipocyte Progenitors in Fetal Rat Bone Cell Populations

Abstract: We investigated the effects of insulin (1-1,000 nM), insulin-like growth factor (IGF)-I, and IGF-II (3-100 nM each) alone or together with 10 nM dexamethasone (DEX) or 10 nM 1,25-dihydroxyvitamin D(3) (1,25[OH](2)D(3)) on proliferation and differentiation of adipocyte and osteoblast progenitors in bone cell populations derived from fetal rat calvaria. The effects on differentiation were evaluated by counting the number of bone or osteoid nodules and adipocyte colonies and the effects on proliferation, by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Local UL treatment did not significantly increase cellular proliferation within the fracture callus, contrary to previous studies examining the effects of insulin and IGF‐1 on fracture healing 17, 18. Others studies suggest that insulin treatment in a non‐diabetic population may not necessarily induce mitogenesis 19, 20. Fulzele et al found that insulin treatment did not affect osteoblast cell proliferation in culture media, compared to untreated osteoblasts 20…”
Section: Discussionmentioning
confidence: 89%
“…Local UL treatment did not significantly increase cellular proliferation within the fracture callus, contrary to previous studies examining the effects of insulin and IGF‐1 on fracture healing 17, 18. Others studies suggest that insulin treatment in a non‐diabetic population may not necessarily induce mitogenesis 19, 20. Fulzele et al found that insulin treatment did not affect osteoblast cell proliferation in culture media, compared to untreated osteoblasts 20…”
Section: Discussionmentioning
confidence: 89%
“…IGF2 is a growth factor that is highly expressed in bone tissue [ 17 ]. A stimulatory effect of IGF2 on cell proliferation, differentiation, and mineralization was demonstrated for rat osteogenic progenitor cells [ 18 ]. We had found in a qRT-PCR analysis that IGF2 was differentially expressed in human DFCs compared with…”
Section: Discussionmentioning
confidence: 99%
“…These comprise a mixture of cells, from primitive mesenchymal stem cells to mature osteoblasts, with precursor cells in between at different stages of commitment [5,6]. This heterogenous cell mix has the potential to differentiate into bone-forming cells/osteoblasts under appropriate conditions using selected hormones/growth factors [7][8][9], vitamins/chemical reagents [10,11] and/or defined surface topographical guidance [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%